A new therapsid from the Permian Madumabisa Mudstone Formation (Mid-Zambezi Basin) of southern Zambia. Issue 4 (3rd July 2016) - Whitney, Megan R.; Sidor, Christian A.
Abstract : Citation for this article: Whitney, M. R., and C. A. Sidor. 2016. A new therapsid from the Permian Madumabisa Mudstone Formation (Mid-Zambezi Basin) of southern Zambia. Journal of Vertebrate Paleontology. DOI: 10.1080/02724634.2016.1150767. http://zoobank.org/urn:lsid:zoobank.org:pub:51F41E55-39EE-4C8E-8474-547A1DC37D2C